General election 2004 : empirical validation of voting pattern in Malaysia - Syed Abdullah Idid, Syed Arabi; Nordin, Mohamad Sahari; Ismail, Nik Ahmad Hisham (Research Center, IIUM, 2007)
The purpose of this study is to test the effects of the politically related socio-economic issues, personality of the new Prime Minister and the perceived strength of the ruling party, Barisan Nasional (BN), in influencing the outcomes of elections. It uses the data from the Star-IIUM Survey 2004 and the official election results of general election 2004 for the three northern states of Malaysia and applies the Structural Equation Modeling (SEM). The study found that the personal attributes of the Prime Minister, the strength of the ruling party and the campaign issues positively influenced the popular votes secured by the BN candidates